Historical analysis of touts as a deviant subgroup in Lagos State-Nigeria (2009)
Over the years, Lagos State has been faced with a cyclical crescendo of unemployed deviant subgroup mainly youths; known as 'Area Boys or Touts' whose activities usually revolves round the transportation corridors of motor parks and bus stops for survival. Though, many scholars have limited their existence to the period of economic recession and the introduction of Structural Adjustment Programmes (SAP) in the 1980s with little or no emphasis on the historical dimension of their growth and development during the period of colonisation. This study traces the emergence of touts to the colonial era and traditional practices of neighbouring communities and states around Lagos under various names like Alikali boys, Boma boys, and jaguda boys which later metamorphose into the present day touts in Lagos state's motor parks and bus stops. Through in-depth interviews and focus group discussions among 150 randomly selected area boys, the study revealed the economic benefits and patronage of touts by Nigerian Politicians and government officials were major factors fostering their continuous existence. The study concludes that so long as area boys/touts serve as a pool from which National Union of Road Transport Workers (NURTW); Road Transport Employee Association of Nigeria (RTEAN) and Politicians employ their staff and bodyguards, it will be difficult if not impossible to eradicate touts from Lagos environment.